THE CONTRIBUTION OF DIGITAL TECHNOLOGY TO ART STUDIO BUSINESS IN JAKARTA - Budiastomo, Denta Mandra Pradipta; Trisnawati, Ida Ayu; Arshiniwati, Ni Made; Sudarta, I Gusti Putu (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
By leveraging technology, empowering people, encouraging innovation, and strengthening organizations, art studios can increase competitiveness while maintaining the relevance of arts and culture in modern society. To develop a business, the combination of technology usually consists of knowledge and physical equipment. Technoware (T), Humanware (H), Infoware (I), and Orgaware (O) are four basic components of development that interact dynamically in the development process. The purpose of this study is to analyze the contribution of digital technology through various digital media to art studio businesses in Jakarta in arts and cultural activities. This research uses quantitative methods, data sources are determined through a purposive sampling technique. Data were collected by direct observation, interviews, Focus Group Discussions, document reviews, and literature studies. The results of this study show the coefficient value of the contribution of digital technology for each technological component of the art studio business for the welfare of artists.